Interactions and evolutionary relationships among bacterial mobile genetic elements - Lang, Andrew S.; Buchan, Alison; Burrus, Vincent (Nature reviews. Microbiology, 2025)
Mobile genetic elements (MGEs) have profound influence on the ecology and evolution of organisms, including bacteria. During the past two decades, a great number of new types of MGEs have been discovered that now seem to be prevalent in diverse bacterial lineages. With the rapid discovery of new categories of MGEs comes an array of new acronyms that present a challenge to grasp. Moreover, it is now clear that there are complex evolutionary connections and molecular interactions among MGEs, and that these entities are not discrete, independent genetic elements acting in isolation. Different types of MGEs share and exchange genes, and coresident MGEs interact with each other within cells, in both cooperative and antagonistic ways. This all greatly affects the end results that are felt by the host organism. In this Review, we strive to clarify emerging bacterial MGE terms and elements while also presenting a comprehensive overview of the current knowledge landscape regarding MGEs in bacteria, their evolutionary relationships and interactions with their host and with one another. In this Review, Lang and colleagues present an overview of the current knowledge landscape regarding mobile genetic elements in bacteria, with a focus on their evolutionary relationships and interactions with each other.